Metodologia para avaliação de cinemática de partículas gasosas em fluidos de viscosidade variável com o tempo e sua aplicação na construção de poços de petróleo - Pinto, Gustavo Henrique Vieira Pereira (2012)
Many challenges have been presented in petroleum industry. One of them is the preventing of fluids influx during drilling and cementing. Gas migration can occur as result of pressure imbalance inside the well when well pressure becomes lower than gas zone pressure and in cementing operation this occurs during cement slurry transition period (solid to fluid). In this work it was developed a methodology to evaluate gas migration during drilling and cementing operations. It was considered gel strength concept and through experimental tests determined gas migration initial time. A mechanistic model was developed to obtain equation that evaluates bubble displacement through the fluid while it gels. Being a time-dependant behavior, dynamic rheological measurements were made to evaluate viscosity along the time. For drilling fluids analyzed it was verified that it is desirable fast and non-progressive gelation in order to reduce gas migration without affect operational window (difference between pore and fracture pressure). For cement slurries analyzed, the most appropriate is that remains fluid for more time below critical gel strength, maintaining hydrostatic pressure above gas zone pressure, and after that gels quickly, reducing gas migration. The model developed simulates previously operational conditions and allow changes in operational and fluids design to obtain a safer condition for well construction